Molecular phylogeny and morphology reveal a new wood-inhabiting fungal species, Hyphoderma guangdongense (Polyporales, Basidiomycota), from China - Su, Jiangqing; Zhang, Xunchi; Zhao, Changlin; Zhou, Hongmin (Phytotaxa, 2024)
Hyphoderma is one of the most important representative groups of wood-inhabiting fungi. These fungi secrete various enzymes capable of degrading cellulose, hemicellulose, and lignin into simple inorganic substances. The taxa within the genus cause the white rot of wood, play a key role in the carbon cycle, and are the most efficient wood decomposers in the forest ecosystem. This study proposes a new wood-inhabiting fungal taxon, Hyphoderma guangdongense, based on morphological features and molecular evidence. It is characterized by the white hymenial surface, a monomitic hyphal system having the generative hyphae with clamp connections, the presence of the septate and tubular cystidia, and cylindrical basidiospores (6–10 × 3–5 µm). The phylogenetic tree inferred from a combination of the internal transcribed spacers (ITS) and large subunit (nrLSU) of the nuclear ribosomal DNA (rDNA) sequences revealed that H. guangdongense placed into the genus Hyphoderma, in which it is closely related to a clade comprising two taxa, H. setigerum, and H. floccosum. A full description, illustrations, and results of the new species' phylogenetic analysis are provided.